Invitation (1937)
018b-0035-001 International Co-ordinating Committee of Aid for Spain On behalf of the above Committee we invite you to attend a Public Meeting in the Friends' Meeting House, Euston Road, N.W.1, to hear reports upon the present position in Spain and the measures being taken to send material aid to the Democratic forces. It will be held on Thursday, March 11th, at 8 p.m. We enclose full particulars. Presidents: VICTOR BASCH. PAUL LANGEVIN. Secretary: MADELAINE BRAWN. M.P.CO. 292/946/18b/35